Navigating the Unknown: Evaluating the Role of FDG PET-CT in Detecting Primary Tumors in Cancer of Unknown Primary- A Five Years Institutional Perspectives in Bangladesh - Zohra, Fatema Tuz; Podder, Priyanka; Alam, Rayhan; Hasnat, Md Abul; Sharmin, Rahima Akter; Hossain, Iqbal; Hossain, Arshad; Yasmeen, Nilufa; Tasnim, Humayra; Alam, Md Jahir; et al. (Bangladesh Journal of Nuclear Medicine, 2025)
Objective: To evaluate the clinical usefulness of 18F FDG PET-CT whole body imaging for identifying primary tumors in patients with cancer of unknown primary (CUP). Methods: A total of 108 patients with an unidentified primary etiology were referred for whole body FDG PET-CT scan from 2019 to 2023 at the Institute of Nuclear Medical Physics, Savar. Visual examination and semi-quantitative analysis (standardized uptake value, SUV) were used to analyze PET-CT images. The utility of FDG PET-CT was evaluated based on formal clinical follow-up findings and histopathological data. Result: The study analyzed 108 cancer patients with CUP aged 19–80 years (mean age: 56.70 ± 13.42 years; males: 65.7%, females: 34.3%). Comorbidities included diabetes (22.2%), hypertension (24.1%), and others. Metastases were frequently detected in cervical lymph nodes (33%), bones (19.4%), and liver (13.9%). Whole-body FDG PET-CT scans identified the primary site in 25% of cases, primarily in the lungs (13.9%), with histopathological confirmation. Histopathology revealed adenocarcinoma (55.6%), squamous cell carcinoma (22.2%), and poorly differentiated carcinoma (11.1%). Pre-scan treatment varied, with 59.3% receiving no prior treatment, while others underwent chemotherapy, radiotherapy, or surgery. The mean SUV was 9.43 ± 11.61. Conclusion: The FDG PET-CT whole-body scan, a non-invasive and sensitive imaging modality, achieved a 25% success rate in identifying primary tumors, enhancing tumor staging, treatment planning, and prognostic accuracy. Bangladesh J. Nuclear Med. 28(1): 39-49, 2025